Tolerance to ischaemia and ischaemic preconditioning in neonatal rat heart - Ostadalova, I; Ostadal, B; Kolár, F; Parratt, J R; Wilson, S (Journal of molecular and cellular cardiology, 1998)
Although there is much information on ischaemic preconditioning in the adult myocardium, this phenomenon has not yet been investigated in neonatal hearts. To examine the early development of cardiac tolerance to ischaemia and the possible protective effects of preconditioning, rat hearts isolated on days 1, 4 and 7 of postnatal life were perfused (Langendorff) with Krebs-Henseleit solution at constant pressure, temperature (37 degrees C) and rate (200 beats/min). Developed force (DF) of contraction was measured by an isometric force transducer, and analysed using an on-line computer. Hearts were exposed to 40 or 60 min of global ischaemia followed by 30 min of reperfusion. Preconditioning was induced by three 3-min periods of global ischaemia, each separated by 5-min periods of reperfusion. Developmental changes in expression of protein kinase C (PKC) isoforms, and their activation following preconditioning, were estimated using Western blot analysis. Recovery of contractile function during reperfusion decreased from day 1 (48 +/- 2%) to day 4 (42 +/- 1%) and day 7 (33 +/- 2%). Preconditioning failed to improve ischaemic tolerance on day 1 (46 +/- 2%) and on day 4 (43 +/- 3%), but pronounced effect was observed on day 7 (40 +/- 2%). Prolonging the period of sustained ischaemia from 40 to 60 min on day 1 did not lead to a better recovery of contractile function in preconditioned hearts. PKC isoforms alpha, delta, epsilon and zeta were expressed in the ventricular myocardium during the first week of life, but there was no evidence of translocation following preconditioning on day 7. It may be assumed that the decreasing tolerance of the heart to ischaemia during early postnatal life is counteracted by the development of an endogenous protection.
Keywords: novorozená zvířata; krysa rodu Rattus; zvířata; potkani Wistar; Ischemic Preconditioning, Myocardial; Animals, Newborn; Isoenzymes; Rats, Wistar; Male; izoenzymy; Myocardial Ischemia; Heart; ischemická choroba srdeční; Protein Kinase C; Rats; myokard; proteinkinasa C; Animals; Myocardium; ischemické přivykání; mužské pohlaví; srdce